Efficacy and Safety of Acupuncture Compared with Standard Treatment in Migraine Without Aura: A Systematic Review of Randomized Controlled Trials - Devanty Anggraini; Rifki Albana (Al Makki Health Informatics Journal, 2025)
Introduction:Migraine without aura is a common neurological disorder that imposes a substantial global burden. While pharmacological therapy remains the cornerstone of treatment, limitations such as side effects, contraindications, and medication overuse highlight the need for complementary approaches. Acupuncture has been proposed as a potential alternative due to its neuromodulatory and analgesic effects. Methods: This systematic review followed PRISMA guidelines and the Cochrane Handbook for Systematic Reviews of Interventions. Searches were conducted in PubMed, ProQuest, SAGE Journals, and EuropePMC, including only randomized controlled trials comparing acupuncture with standard pharmacological treatments in migraine without aura. Outcomes of interest included headache frequency, intensity, acute medication use, quality of life, and safety. Risk of bias was assessed using the Cochrane RoB 2.0 tool. Results: Eight randomized controlled trials involving patients with migraine without aura were included. Acupuncture consistently reduced migraine frequency, with greater decreases in headache days and attack frequency compared with drugs such as flunarizine and valproic acid. Significant reductions in pain intensity were observed in several studies, with acupuncture showing either comparable or superior effects relative to pharmacological therapy. Acupuncture also led to earlier and more sustained reductions in acute medication use, potentially lowering the risk of medication overuse headache. Quality of life improvements were reported in domains of physical function, emotional well-being, and migraine-specific indices. Adverse events were generally mild and transient (e.g., local bleeding, discomfort), and occurred less frequently than with standard medications, which were associated with drowsiness, weight gain, or gastrointestinal symptoms. Discussion and Conclusion: Acupuncture demonstrates favorable efficacy and safety compared with standard pharmacological treatments in migraine without aura, offering reductions in frequency, intensity, and medication use, alongside improvements in quality of life. Given heterogeneity in protocols and some methodological limitations, further large-scale multicenter trials with standardized designs are warranted to confirm these findings and guide clinical practice.